Analisis Kerapatan Vegetasi Kecamatan Ambarawa dengan Algoritma NDVI - Rafsanjani, Mohammad Alifian; Papilaya, Frederik Samuel (Universitas Pendidikan Ganesha, 2024)
This study analyzes changes in vegetation density in Ambarawa District, Semarang Regency, using the Normalized Difference Vegetation Index (NDVI) algorithm based on Landsat-8 OLI satellite imagery. Data from 2019 (low rainfall: 599 mm²) and 2022 (high rainfall: 2202 mm²) were compared to assess the impact of climate variability on vegetation. Results indicate that NDVI values in 2019 ranged from -0.31 to 0.79, with sparse vegetation dominating (36.12%). By 2022, NDVI values improved to -0.28–0.84, showing a significant increase in dense vegetation (+10.21%). The analysis demonstrates that rainfall significantly influences vegetation density, with wet seasons enhancing vegetation health and coverage. This study recommends routine NDVI-based monitoring for sustainable environmental planning. Validation using Google Earth confirms the findings' accuracy. Future research should incorporate field surveys and anthropogenic factor analysis for more comprehensive insights.